Endividamento familiar: um estudo no município de Sant’Ana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This article explores the impact of family debt on today's society, with a greater focus on the municipality of Santana do Livramento, where research was carried out revealing that many homes face financial difficulties. The research establishes that the majority of individual families use loans, credit cards and financing to cover day-to-day expenses, such as food, education and health, often resorting to credit to compensate for insufficient monthly income. This article shows that among the main causes of debt are the lack of financial planning, easy access to credit and high interest rates. The research also highlighted that a large proportion of families do not have emergency reserves, which worsens the situation when unforeseen expenses arise, another relevant factor is low financial education. To deal with these issues, the study recommends the promotion of financial education initiatives, especially aimed at long-term planning and the conscious use of credit. Furthermore, it suggests encouraging the development of local policies to support individual families, reducing economic vulnerability and improving the quality of life of Santana do Livramento residents. In this article, the approach through quantitative research was used by using a statistical instrument and collecting data to measure the variables.
Family indebtedness: a study in the municipality of sant’ana do livramento
Keywords: Endividamento familiar; Inadimplência; Educação financeira; Planejamento financeiro; Family debt; Default; Financial education; Financial planning; CIENCIAS SOCIAIS APLICADAS